Analysis of Strategic Business Planning for a New Pharmacy in the Depok Area - Putra, Gunawan Satria; Saragih, Sahat; Hatta , Iha Haryani (Jurnal FARMASIMED (JFM), 2025)
This study evaluates the business strategies of new pharmacies in Depok post the Covid-19 pandemic, which experienced significant growth. Despite the emergence of numerous new pharmacies in 2024, their management is deemed to fall short of pharmaceutical standards. This research aims to analyze the implemented business strategies, their alignment with vision and mission, and relevant strategies for performance improvement. The research method employed is descriptive qualitative, utilizing SWOT analysis as a data analysis tool. Data collection was conducted through in-depth interviews with 9 informants from 6 pharmacies and a concise survey. The respondents were pharmacy owners and managers. The findings indicate that these six pharmacies lack a structured business strategy plan. The primary performance metric used is sales turnover. Business vision and mission have not been established, hindering the alignment of business strategies. Implemented business strategies remain normative, such as promotions via brochures, pamphlets, and discounts. The resulting business strategy recommendations encompass two key aspects: fulfilling pharmaceutical service standards and enhancing financial performance. Pharmaceutical service standards include drug consultation, medical records, drug availability, patient education, and legal compliance. Financial performance improvement can be achieved through price adjustments, operational cost efficiency, sales growth, inventory management, service diversification, and customer satisfaction. It is recommended that pharmacies engage with local communities to socialize programs and services. Informal approaches are considered more effective.